Development of Health Kiosk Prototype for Blood Pressure and Fat Mass Measurement - Umiatin, Umiatin; Putri, Pinkan Amanda; Purwalaksana, Ahmad Zatnika; Al Farizy, Firnas; Nurdin, Muhammad; Purnama, Bedy; Ifa, Rista Putri Nur; Abidin, Muhammad (Journal of the Physical Society of Indonesia, 2025)
Health development in Indonesia faces a double burden of disease, namely infectious and non-communicable diseases (NCDs), with cardiovascular diseases (CVDs) accounting for nearly half of NCD-related deaths. Major CVD risk factors are hypertension and obesity, which can be controlled through routine monitoring of blood pressure and body mass index (BMI). This study aims to develop a health kiosk prototype integrating a sphygmomanometer and BMI–fat analyzer. The research consists of three stages: characterization of sensors for blood pressure and body fat measurement, comparison of proximity sensors, and prototype testing. The MPX5050GP pressure sensor achieved an R² of 1 with a sensitivity of 0.012 volts. Proximity sensor characterization showed R² values of 0.9996 (HC-SR04) and 0.9997 (JSN-SR04T), with sensitivities of 0.9943 cm and 0.9831 cm, respectively. The load cell reached an R² of 1 with a sensitivity of 1.0056 kg, while the AD5933 impedance showed R² = 1 and a sensitivity of 0.9999 Ω. Prototype trials with ten samples indicated that blood pressure, BMI, and fat mass measurements were feasible but not yet optimal, with errors in height measurement and limitations in the blood pressure algorithm. Despite these challenges, the successful integration of the sphygmomanometer and BMI–fat analyzer was achieved.